Alternatif Rekomendasi Kebijakan Pengendalian Faktor Risiko Ergonomi Terhadap Penggunaan Komputer : Alternative Recommendations for Ergonomic Risk Factor Control Against Computer Use - Budiprastiwi, Rosyana Mei; Rindu (Journal of Public Health Education, 2022)
Introduction: Using computers is considered to increase work effectiveness and efficiency, but it can also cause bone and muscle disorders (low back pain and carpal tunnel syndrome). Internal data from physical environmental inspections at PT X shows that there has been an increase in the number of complaints caused by ergonomic risk factors from 2017 to 14 workers due to awkward body positions when working using computers. Objective: This research aims to determine efforts to control ergonomic risks in computer use at PT X. Methods: This research uses a qualitative descriptive method by collecting primary and secondary data. Primary data was obtained from observations (RULA) and in-depth interviews. Meanwhile, secondary data was obtained through literature studies and internal data from physical environmental inspections. Results: This research shows that PT X does not yet have studies, policies, guidelines, and SOPs regarding controlling ergonomic risk factors for computer use. Therefore, an examination of the physical environment related to ergonomic risk factors has not been carried out. So that ergonomic risk control for workers who use computers can be implemented properly, there need to be studies, policies, guidelines, and Standard Operating Procedures (SOP) regarding controlling ergonomic risk factors for computer use that refer to the Law on Office K3. Conclusion: Characteristics of ergonomic risk factors for computer use found in PT X such as work posture, work duration, work desks, work chairs, and workstations are not following office ergonomics standards regulated in Minister of Manpower Regulation No. 48 of 2018 concerning office ergonomics standards. The ergonomic assessment method in offices is using the RULA assessment method, but at PT X this has not been implemented.